2009
DOI: 10.1142/s0192415x0900720x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Ursolic Acid fromCornus officinalison the Hydrogen Peroxide-Induced Damage of HEI-OC1 Auditory Cells

Abstract: The fruits of Cornus officinalis have been used in traditional oriental medicine for treatment of inner ear diseases, such as tinnitus and hearing loss. In the present study, we investigated the protective effect of C. officinalis on hydrogen peroxide-induced cytotoxicity in HEI-OC1 auditory cells. The results from bioassay-guided fractionation of methanol extract of C. officinalis fruits showed that ursolic acid is a major active component. Ursolic acid (0.05-2 microg/ml) had protective effect against the HEI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 28 publications
1
14
0
2
Order By: Relevance
“…In a previous paper, we showed that UA had chemoprotective activity against tBHP-induced DNA damage in HepG2 cells [24]. Our results are in agreement with other reports that also show that UA protects against H 2 O 2 -induced DNA damage [28,29] Besides DNA SBs, 8-oxoGua is one of the most abundant forms of oxidative damage and has been shown to cause G to T transversions. To evaluate effects on DNA protection against 8-oxoGua formation, we exposed Caco-2 cells to Ro plus visible light (to induce 8-oxoGua).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a previous paper, we showed that UA had chemoprotective activity against tBHP-induced DNA damage in HepG2 cells [24]. Our results are in agreement with other reports that also show that UA protects against H 2 O 2 -induced DNA damage [28,29] Besides DNA SBs, 8-oxoGua is one of the most abundant forms of oxidative damage and has been shown to cause G to T transversions. To evaluate effects on DNA protection against 8-oxoGua formation, we exposed Caco-2 cells to Ro plus visible light (to induce 8-oxoGua).…”
Section: Discussionsupporting
confidence: 92%
“…The protective effect of UA has been attributed to the ability of UA to increase levels of non-enzymatic antioxidants such as glutathione (GSH) and to increase the activity of antioxidant enzymes such as catalase (CAT), glutathione peroxidase (GPX) and superoxide dismutase (SOD) [29,41,42]. Martin-Aragon et al [43] reported that UA restores hepatocyte antioxidant levels preventing carbon tetrachloride-induced liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Galactosides of cyanidin ( 58 ) and pelargonidin ( 53 ) detected in both species inhibited lipid peroxidation by 70.2 and 40.3% in an iron-catalyzed liposomal model, respectively (Seeram et al, 2002). On the other hand, the antioxidant properties, including protection of catalase and glutathione peroxidase, of C. officinalis fruits are also assigned to polysaccharides (Li et al, 2012; Wu et al, 2013) and ursolic acid (Yu et al, 2009). …”
Section: Similarities and Differences Of Pharmacological Effects Or Bmentioning
confidence: 99%
“…Besides quercetin and rutin, we reported that ursolic acid (a triterpenoid) protect against DNA damage induced by tert-butyl hydroperoxide (t-BHP) in HepG2 cells (Ramos et al, 2008). Other reports showed that ursolic acid and/or luteolin protect DNA from damage induced by H 2 O 2 , t-BHP or AZT (3_-azido-3_-dideoxythymidine) in several cell lines, such as leukemic cells, HEI-OC1 auditory cells and PC12 cells (Horvathova et al, 2003;Horvathova et al, 2004;Ovesna et al, 2006;Yu et al, 2009;Noroozi et al, 1998;Silva et al, 2008). Rosmarinic acid (RA), reduced the frequency of micronuclei and the extent of DNA damage induced by doxorubicin in V79 cells (Furtado et al, 2009).…”
Section: Polyphenolsmentioning
confidence: 99%